Refuse dump land reclamation soil - ZHENG JIYONG; REN ZHISHENG; ZHANG XINGCHANG; QI RUIPENG (2017)
The utility model relates to a refuse dump land reclamation soil, be mining area solid waste, arsenic sandstone layer, soil layer in proper order including from the bottom up. The utility model discloses make the soil moisture that keeps that refuse dump land reclamation soil can be fine, make soil erosion and water loss very alleviate, promote ecological the recovering, the utility model discloses a refuse dump land reclamation soil is effectual have been solved current shanxi shan and covers the mining area refuse dump and because of the earthing layer thickness not enough liquid manure leakage problem who produces, compensatied loess and sand and soil guarantor preserve moisture and fertility subalternation shortcoming. 本实用新型是关于种排土场复垦土壤，包括从下到上依次为矿区固体废弃物，砒砂岩层，土层。本实用新型使排土场复垦土壤能够很好的保持土壤水分，使水土流失大为减轻，促进生态恢复；本实用新型的排土场复垦土壤有效的解决了当前晋陕蒙矿区排土场因所覆土层厚度不足而产生的水肥渗漏问题，弥补了黄土和沙土保水保肥差等缺点。